Association between serum bicarbonate and 28-day mortality in critically ill patients with infective endocarditis: a cohort study from MIMIC-IV - Yingxiu Huang; Ting Ao; Peng Zhen; Ming Hu (Scientific Reports)
Abstract The relationship between bicarbonate level and mortality in critically sick patients with infective endocarditis (IE) is currently not well established. The MIMIC-IV database was used to provide data for a retrospective cohort research. Included were patients with IE who were hospitalized to the critical care unit (ICU). Within the first 24 h following ICU admission, the serum bicarbonate was assessed. The 28-day mortality was the end-point result. To evaluate the relationship between the serum bicarbonate and 28-day mortality, multivariable Cox regression was employed. The study included 450 patients with IE in serious condition in the ICU, with a 57.4-year-old average and 64.2% male representation. The 28-day mortality rate stood at 20%. Unadjusted analysis revealed that higher serum bicarbonate levels upon ICU admission were significantly linked to reduced 28-day mortality (hazard ratio [HR], 0.90; 95% confidence interval [CI], 0.85–0.95; p < 0.001). This correlation remained significant after adjusting for potential confounding factors (adjusted HR, 0.94; 95% CI 0.89–0.99; p = 0.028). When categorizing bicarbonate levels, patients in the highest group (T3, ≥ 25 mEq/L) showed a significantly decreased adjusted HR of 0.55 (95% CI 0.33–0.93; p < 0.001) in relation to the control group (T1, ≤ 22 mEq/L) in the final model. Consistent results were observed in subgroup analyses across various groups. In patients with IE in the ICU, elevated serum bicarbonate upon admission was independently linked to a lower 28-day mortality. These findings indicate that serum bicarbonate can serve as a prognostic marker, supporting the process of risk assessment and providing direction for the clinical care of patients with IE.